2003
DOI: 10.1556/abiol.54.2003.3-4.6
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of substance P containing nerve fibres and their contacts with mast cells in the diabetic rat's tongue

Abstract: Sensory neuropathy is common symptom of the diabetes mellitus and the prevalence of oral lesions is higher in diabetic patients. The distribution of substance P was studied immunohistochemically in streptozotocin induced diabetic rat's tongue. The morphological association of sensory nerves (substance P immunoreactive) with mast cells (nerve fibre-mast cell contact) was monitored. The substance P nerve fibre mast cell contacts were very scanty in control tongue. The number of substance P nerve terminals and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…It was demonstrated that calcitonin gene-related peptide (CGRP) and substance P (SP) nerve fibers innervate the mucosal and submucosal vessels of the upper gastrointestinal tract [7,8]. SP and CGRP are thought to be the mediators of neurogenic inflammation [9][10][11]. Peptides synthesized in primary sensory neurons are released through the axon reflex from small-diameter fibers in the peripheral tissues near blood vessels and they may act as neurogenic mediators of inflammation and pain.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that calcitonin gene-related peptide (CGRP) and substance P (SP) nerve fibers innervate the mucosal and submucosal vessels of the upper gastrointestinal tract [7,8]. SP and CGRP are thought to be the mediators of neurogenic inflammation [9][10][11]. Peptides synthesized in primary sensory neurons are released through the axon reflex from small-diameter fibers in the peripheral tissues near blood vessels and they may act as neurogenic mediators of inflammation and pain.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the number of SP-reactive fibers and mast cell-nerve contacts have been reported as parts of the pathology of several diseases (3,19,45). SP can activate mast cells both through binding of the neurokinin-1 receptor present on these cells (8) and through receptor-independent mechanisms (10).…”
mentioning
confidence: 99%
“…Streptozotocin-induced diabetic rats showed significant increases in mesenteric artery weight, wall-to-lumen ratio, arterial wall ECM deposition, and gene expression of epidermal growth factor (EGF) and TGF-β1 [97]. In those rats, diabetes also associated with an increase of mast cell numbers to the tongues [98] and in mesenteric vessels [97] — often associated with fibrosis, a common feature of diabetic microvascular complications [35]. In those experimental diabetic rats, treatment with the mast cell degranulation inhibitor tranilast (N-[3,4-demethoxycinnamoyl]-anthranilic acid) reduced mesenteric vessel fibrosis, artery weight, wall-to-lumen ratio, and matrix deposition, although it did not influence tryptase-positive mast cell infiltration, plasma glucose level, or systolic blood pressure [35, 99].…”
Section: Mast Cell Chymases and Tryptases In Metabolic Diseasesmentioning
confidence: 99%